OPTIMALISASI PENDISTRIBUSIAN LOGISTIK OLEH DENBEKANG IV-44-033/SALATIGA DALAM MENDUKUNG PENANGANAN BENCANA ALAM - Siregar, Paulina; Supriyono, Tjatur; Panji, Muhammad (PPM Sdirjianbang Akademi Militer, 2023)
The National Agency for Disaster Countermeasure (BNPB) represents the focal point of government agencies at the central level. In the meantime, the local disaster resistant point at the state and district/ city is a Local Disaster Relief Agency (BPBD). From the non-formal side, both of the national and local level forums have been set up in order to amplify disaster barriers in Indonesia. At a national level, it has formed a national platform (Planas) which consists of many elements such as civil society, business world, college, media and international agencies. This research uses qualitative methods. The regional command unit has also become a local level in the natural disasters’ relief as well as it’s empowered the disaster area. However, it is an obligation for Denbekang IV-44-033/Salatiga to support the area in disaster relief. The government that acts as a regulator in carrying out these functions can be felt less optimized since the distribution of the logistics to the natural disasters regions is done after (The National Agency for Disaster Countermeasure) incapable to cope with the disasters’ victims especially in the logistics maximally. The result of this research is that the implementation of the distribution of logistics for natural disaster management which has been conducted by Denbekang IV-44-03 /Salatiga is considered less optimal due to a lack of communication between Denbekang IV-44-03 /Salatiga as a part of the units (BNPB and local governments) that assisting in handling natural disaster. The facilities and infrastructures are less representative in encountering the natural disaster as a part of Military Operation Other Than War (OMSP) which is to undertake the task of handling natural disasters. Those problems can be overcome by the ability of the military personnel who has the education and rank background which has made the task execution easier. Another problem that arises is the channel of the request for assistance from the local government to Denbekang IV-44-03/Salatiga to cope with natural disasters is winding up which makes late respond.